Relationship between Leptin gene and some growth traits in local Awasi sheep - Kadhim, Abd J.; E.K., AL-Zargani; AL-Anbari, N. N. (Journal of Kerbala for Agricultural Sciences, 2017)
This investigate had been conducted in the First Research Station for Agriculture College Muthana University and the laboratory of biological technique & practical analysis - Ministry of Science and Technology through the period 1/11/2015 to 1/07/2017. The aims of this study was to the relationship of genetic components of Leptin gene and some of traits for local sheep sheep. The growth parameters had been variant which are lamb weights are at birth and weaning , weight average raise between birth and weaning significantly (P<0.05) with the variant of the genotype of Leptin gene of their mother for the genotype AB and AA, but the body dimensions which had been studied at birth and at weaning except body height (P<0.05) and chest circumference (P<0.01) at weaning with genotype variation for this gene, Additionally, the application of this study on larger sample for many production seasons can give more accurate results to adopt exclusion and replacement strategy.